New experiments with a double crystal electron interferometer - Tavabi, Amir H. (2018)
Recent advances in transmission electron microscopy and specimen preparation now permit the revival of an old idea, originally pioneered by Marton, of using single crystals as amplitude division beam splitters. As a first step in the direction of realizing a three crystal electron interferometer, we present results obtained from a double crystal interferometer, in which the gap between the two crystals is under experimental control and perfect registry is obtained by using focused ion beam milling to fabricate the interferometer from a single Si crystal.